Steady-state security region of energy hub: Modeling, calculation, and applications. (February 2021) - Yong, Pei; Wang, Yi; Capuder, Tomislav; Tan, Zhenfei; Zhang, Ning; Kang, Chongqing
Highlights: The steady-state security region of the energy hub is defined and formulated. An efficient approach is proposed to calculate the security region. Critical components of the system are identified using security region analysis. The security region is used in multi-energy systems planning. Abstract: Multi-energy systems (MES) provide various types of energy services by coupling different energy sectors. Such coupling increases the efficiency and flexibility of the entire energy system, and at the same time, however, increases the dependencies of the load carrying capability among different types of load demand. In the MES planning stage, we always want to assess and compare the load carrying capability among different planning schemes, considering the N-1 or N-M contingencies and the mutual effect of different energy sectors. While in the MES operation stage, we always want to know if the load of MES can be securely supplied considering potential contingencies and how far the current operation status is from the security boundary. This paper proposes a new concept named the energy hub (EH) security region and applying the concept to depict the load carrying capability of the district MES. The concept defines a region in a hyperspace where the MES can be safely operated under steady-state operational and security constraints. We first model the district MES using the EH approach and propose the mathematical form of the EH steady-state security region systematically. Then, a vertex-based algorithm is proposed to precisely calculate the security region using a space projection technique. We further propose indices to evaluate the load carrying capability of a district MES and identify critical components. Numerical case studies are conducted on two test systems to verify the validity of the proposed method. The results show the proposed EH security region concept and calculation method provide quantitive indicators on how to compare MES planning schemes and improve the load carrying capability.